1994
DOI: 10.1093/rheumatology/33.7.677
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Peri-Articular Soft Tissue Finger Swelling in an Adolescent Male: Pachydermodactyly or Pachydermoperiostosis?

Abstract: Benign soft tissue swelling affecting the interphalangeal joints can sometimes be misdiagnosed as an arthropathy. Garrods fatty pads (knuckle pad syndrome) is a relatively common and harmless condition characterized by discrete fibromatous skin pads over the dorsum of the interphalangeal joints. We describe a case which clinically resembles the rare but benign condition of pachydermodactyly with some pathological features of the distinct syndrome of pachydermoperiostosis. The possibility of an overlap syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Unrecognized or ig- nored by most rheumatologists, there were only 3 case reports in the international rheumatology literature so far. [3][4][5] No racial or ethnic association has been evaluated. In Asia, 1 case from Taiwan 6 and 4 cases from South Korea 7,8 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Unrecognized or ig- nored by most rheumatologists, there were only 3 case reports in the international rheumatology literature so far. [3][4][5] No racial or ethnic association has been evaluated. In Asia, 1 case from Taiwan 6 and 4 cases from South Korea 7,8 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…КлиничесКая дерматология и венерология 4,2016 Наследственная патология соединительной тка-ни представляет собой уникальную онтогенетиче-скую аномалию тканевой структуры, проявляющую-ся в уменьшении содержания отдельных видов кол-лагена или изменения их соотношения, что приво-дит к снижению прочности соединительной ткани органов и систем [9][10][11]. Следствием этого является расстройство гомеостаза на тканевом, органном и организменном уровнях, что сопровождается раз-личными морфофункциональными нарушениями висцеральных и локомоторных систем с прогреди-ентным течением [12,13].…”
Section: случай из практикиunclassified
“…Staining by Alcian blue reveals a mucin deposit. 37,39,40,42,47,57 An increase can also be observed in the thickness of the basal membrane, 33 augmented eccrine sudoriparous glands, various of which are fibrose, and intense deposit of mucopolysaccharides, 34 poor demarcation between the papillary and reticular dermis, 35 marked eosinophilia 36 and lymphocytic infiltrate. 37 Histochemical study of the collagen fibers showed them to be collagen I, III and V. Under electron microscopy the collagen fibers are finer than those of normal tissues.…”
Section: Caso Clínicomentioning
confidence: 99%
“…A coloração pelo alcian blue evidenciou depósito de mucina. 37,39,40,42,47,57 Podem ser também observados aumento da espessura da membrana basal, 33 aumento das glândulas sudoríparas écrinas, várias fibrosadas, e intenso depósito de mucopolissacarídeos, 34 pobre demarcação entre derme papilar e reticular, 35 marcada eosinofilia 36 e infiltrado linfocitário. 37 Estudo histoquímico das fibras de colágeno mostrou serem colágeno I, III e V. Pela microscopia eletrônica as fibras de colágeno são mais finas do que as dos tecidos normais.…”
Section: Introductionunclassified